2017
DOI: 10.1021/acs.jafc.6b04899
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Swelling and Responsive Properties of Pineapple Peel Carboxymethyl Cellulose-g-poly(acrylic acid-co-acrylamide) Superabsorbent Hydrogel by the Introduction of Carclazyte

Abstract: The superabsorbent hydrogels were synthesized by grafting acrylic acid and acrylamide onto pineapple peel carboxymethyl cellulose and effect of carclazyte introduction was compared. The structure and morphology of the superabsorbents were investigated by Fourier transform infrared spectroscopy, X-ray diffraction, and field emission scanning electron microscopy. Swelling behaviors of the superabsorbents were investigated in distilled water, 0.9% NaCl solution, various salt and pH solutions, as well as surfactan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(57 citation statements)
references
References 49 publications
(86 reference statements)
3
54
0
Order By: Relevance
“…With pH higher than 7, the RR will also decline with the rise of pH value. In this stage, the “charge screening effect” of excessive Na + ions cannot be neglected . The electrostatic attractions among COO − and Cu 2+ would suffer from this screening effect, causing a declined RR.…”
Section: Resultsmentioning
confidence: 99%
“…With pH higher than 7, the RR will also decline with the rise of pH value. In this stage, the “charge screening effect” of excessive Na + ions cannot be neglected . The electrostatic attractions among COO − and Cu 2+ would suffer from this screening effect, causing a declined RR.…”
Section: Resultsmentioning
confidence: 99%
“…log q e = logK F + 1 n logC e (8) where K F ((mg g -1 )(L mg -1 ) 1/n ) and n (dimensionless) are the constants of the Freundlich model. The parameters of the Langmuir and Freundlich isotherm are summarized in Table 3, showing that R 2 values of the Langmuir adsorption isotherm were consistently higher than those for the Freundlich adsorption isotherm.…”
Section: Effect Of Initial Concentration On Heavy Metal Ions Adsorptimentioning
confidence: 99%
“…For example, 2‐acrylamido‐2‐methylpropanesulfonic acid (AMPS) is a widely applied chemical agent containing sulfonic acid and amide groups, which is grafted to the hydroxyl group of the CMC backbone . Previous studies have reported that the functionalization of CMC with either AMPS or other comonomers using a conventional thermal method had the disadvantages of time consuming synthesis and low gel content yield . Therefore, it is necessary to improve the synthesis process for CMC‐based hydrogels for commercial viability and structure of the hydrogel to increase the adsorption efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The eco‐friendly, efficient extract and reutilization of fruit residues1 is one of the critical issues in sustainable agricultural development 2,3. In the process of red‐wine production,4 grape pomace of about 9 000 000 t per year was generated in China, which was urgently recycled and reutilized 5,6.…”
Section: Introductionmentioning
confidence: 99%